XAVIER RIDDLE AND THE SECRET MUSEUM : I am Mary Anning - Vitale, Brooke (New York : Penguin Young Readers, an imprint of Penguin Random House LLC, 2021)
"Xavier, Brad, and Yadina are off on a fossil hunt with paleontologist Mary Anning! She helps them learn that when you start something it feels good to finish it"-- Provided by publisher
"Based on the best-selling series by Brad Meltzer and illustrated by Christopher Eliopoulos"--Cover.
"Based on: Ordinary people change the world"--Back cover.
Keywords: Anning, Mary, -- 1799-1847; Paleontologists -- Juvenile literature; Museums -- Juvenile literature; Children stories, English